L’espace urbain en tant que lieu d’expérience d’une altérité “exilique”Réflexions sur les romans Cités à la dérive et Printemps Perdu de Stratis Tsirkas - Evangelia Tsakiropoulou (Cahiers Balkaniques)
This article examines cities as settings for experiencing ‘exilic’ otherness, drawing on Stratis Tsirkas’s trilogy, Drifting Cities, and his novel, Lost Spring. By choosing cities characterized by social and cultural diversity, Tsirkas evokes the experience of displacement from oneself to the other and the peculiarity of being ‘the other’. The characters’ status as refugees or clandestine individuals leads them to continuous displacement and to confront both the elsewhere and the other. While geographical exile prompts physical displacement, intimate exile leads to self-awareness and proves to be an enriching experience that results in “reterritorialization” in a new city. However, the city can also become a place of encounter with negative otherness. In this case, the elsewhere is felt as an unsettling space, and the other as a threat. The experience of otherness might resemble a ‘katabasis’, a descent, deep within oneself, which allows one to discover the elsewhere and the other, and to discover oneself.